PENGARUH POLITICAL TRUST TERHADAP PARTISIPASI DALAM GERAKAN MAHASISWA DENGAN POLITICAL EFFICACY SEBAGAI MEDIATOR - Arini Hidayanti; Siti Nurhidayah (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2021)
This study aims to determine the effect of political trust on participation in student movements by involving political efficacy as a mediator. This research is a quantitative study involving 123 students from the Islamic University